Kualitas Kepemimpinan Kepala Sekolah dan Kinerja Guru dalam Meningkatkan Hasil Belajar Siswa di SD Swasta Kota Batam - Erni Suryani; Abdul Mujib; Sardjijo Sardjijo (Universitas Kristen Satya Wacana, 2021)
This study is to describe the leadership quality of the principal, teacher performance, and the principal's efforts in improving student learning outcomes during the pandemic at SD IT Harapan Insani and Mambaul Ulum Batam. The research method uses descriptive qualitative. The research subjects were principals and teachers at SDIT Harapan Insani and Mambaul Ulum. Interview, observation, and documentation methods were used as data collection techniques. Data analysis techniques include data reduction, data presentation and drawing conclusions. The results showed that (1) the leadership quality of the principal in improving teacher performance was in accordance with the research indicators, namely the principal as an innovator, supervisor, and motivator. (2) The performance of teachers during learning in the Covid-19 pandemic has been in accordance with research indicators, namely the ability to plan, carry out learning activities, and conduct evaluations, but it is not maximized, there are still teachers who have not been able to control the class during online learning (3) School principals' efforts to improve teacher performance during the Covid-19 pandemic are: (a) ensuring learning plans are in accordance with conditions, (b) online learning (c) evaluation with direct monitoring, (d) developing teacher professionalism (e) quality improvement and (f) provision of wifi/internet facilities in schools. (4)The impact of the quality of the principal's leadership and teacher performance has a positive effect on improving the Civics learning outcomes of fourth grade students at the Integrated Islamic Elementary School (SDIT) Harapan Insani and Mambaul Ulum Batam.